PENGUKURAN DOSIS RADIASI ORGAN TYROID KELUARGA PASIEN PADA PEMERIKSAAN CT SCAN KEPALA PEDIATRIK - Ayu Wita Sari; Maizza Nadia Putri; Fajril Musrifah (LPPM STIKes Awal Bros Pekanbaru, 2022)
Pediatric Ct Scan is a quick and painless examination that uses x-ray equipment to create detailed images of the child’s internal organs, bones, soft tissues and blood vessels. Pediatric Ct Scan examinations are used to help diagnose abdominal pain and evaluate trauma injuries. This type of research is quantitave research using analytical observational methods, this research has been done on 25 April- 16 June 2022 with 10 patient’s famillies as research sample. Measurement of the radiation dose of the tyroid organ of the patien.s famillis using a DMC 300 pendose measuring instrument by means of a tool tied to the left side of the patient’s famillies neck (the part that is not covered by the apron). The results of the study of the radiation dose of the tyroid organs of the patient’s family produced avarage for a scanogram of 0,001 mSb, for scanning results an average of 0,0187 mSv was obtained, the average value of the quivalent dose was 0,0187 mSv and the average value of the effective dose was 0,0000748 mSv. The average obtained is still categorized as safe for the general public when compared to PERKA BAPETEN no.8 of 2011.